2017
DOI: 10.3324/haematol.2016.155184
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric antiphospholipid syndrome: early variations of angiogenic factors are associated with adverse outcomes

Abstract: The prognostic value of angiogenic factors in newly pregnant women with obstetric antiphospholipid syndrome (oAPS) has not been documented. We observed 513 oAPS who experienced three consecutive spontaneous abortions before the 10th week of gestation or one fetal loss at or beyond the 10th week. We assessed the plasma concentrations of the proangiogenic factor placenta growth factor (PIGF) and of the antiangiogenic factor soluble fms-like tyrosine kinase-1 on the eve and on the 4th day of the low-molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Recent research [ 33 ] revealed a link between an imbalance in angiogenic factors and early-onset preeclampsia, characterized by elevated levels of soluble fms-like tyrosine kinase-1 and decreased placental growth factor. Abnormal PlGF-to-sFlt-1 ratio holds negative predictive value for adverse obstetric and neonatal outcomes in APS [ [34] , [35] , [36] ]. These findings support the investigation of angiogenesis-related biomarkers as a viable approach to detecting early-onset preeclampsia in patients with OAPS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research [ 33 ] revealed a link between an imbalance in angiogenic factors and early-onset preeclampsia, characterized by elevated levels of soluble fms-like tyrosine kinase-1 and decreased placental growth factor. Abnormal PlGF-to-sFlt-1 ratio holds negative predictive value for adverse obstetric and neonatal outcomes in APS [ [34] , [35] , [36] ]. These findings support the investigation of angiogenesis-related biomarkers as a viable approach to detecting early-onset preeclampsia in patients with OAPS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NOH-ANGIO study, 43 an ancillary study to the NOH-APS, showed that the early LMWH-induced variations in placental growth factor and sFlt-1 concentrations in newly pregnant oAPS women may help to detect patients at a low risk of placental diseases, due to the high negative predictive value of their ratio of variations (0.92).…”
Section: Late Pregnancy Placental Diseasesmentioning
confidence: 99%
“…The use of complement inhibitors restored the balance and improved fetal outcomes 71 . Two studies concluded that an early assessment of PlGF:sFlt1 ratio could serve as biomarker, displaying good negative predictive values for severe pregnancy adverse events 72,73 …”
Section: Management Of Obstetric Aps: Whom and How Should We Treat?mentioning
confidence: 99%